Tanzania: Business Information Services (BIS) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Business Information Services (BIS) has set up a network of district centres where farmers can access online information on the prices and availability of farm inputs such as fertilizers, seeds and pesticides.